Studi komparasi kitab Qowaidul Imla’ Fii ‘Ashrah Durus Sahlah dan kitab Qowaidul Imla’ - Khisbulloh, Afan (Maliki Interdisciplinary Journal, 2024)
Comparative research is research that is intended to find out and or test the differences between two or more groups. Comparative research is also research conducted to compare a variable (object of research), between different subjects or different times and find the cause-and-effect relationship. The purpose of our research is to analyze the differences and similarities between 2 books in the field of Arabic, namely, " قواعد الإملاء " and " قواعد الإملاء في عشرة دروس سهلة". In this analysis we found significant differences and similarities in general, these two books both explain the rules of good and correct Arabic writing which is certainly very useful for all those who study the field of Arabic, especially students of Arabic Language and Literature. This book can be used as a reference for deepening understanding in the Qowaidul Imla course. In terms of writing these two books have differences in the book " قواعد الإملاء في عشرة دروس سهلة" more detailed while the book " قواعد الإملاء " writing material is more brief and organized. And there are also differences in terms of language and material